The Culture Industry and Loss of Individuality in Aldous Huxley’s Brave New World - Özenç, Ardeniz (Advances in Social Sciences Research Journal, 2022)
When Theodore W. Adorno and Max Horkheimer, two of the most prominent figures of Frankfurt School, published their work Dialectic of Enlightenment in 1947, the Second World War had shaken the world and almost all hopes for humanity’s salvation were lost. The grand narratives such as Marxism, which had previously announced the coming of a fair and just revolution for the oppressed, and Humanism, which pointed the way to a harmonious existence of all humans, were all abandoned because the wars had shattered humanity’s hope in its own capabilities to achieve these ideals. Adorno and Horkheimer feared the dangers totalitarian and capitalist societies imposed on their citizens. Their assertion that late capitalism created a ‘culture industry’ which is used for the stupefaction and subjugation of people by turning them into uncritical masses is exemplified in Aldous Huxley’s novel, Brave New World. Huxley illustrates some of the key points that critical theory scholars make, such as commodification of culture, and alienation and reification of the individual. It is the aim of this research to analyse Brave New World in terms of Adorno and Horkheimer’s concept of ‘culture industry’, as specified in Dialectic of Enlightenment and the aforementioned key concepts of critical theory.